Anti-Collapsin Response Mediator Protein 5(CV2/CRMP5) and Anti-Glutamic Acid Decarboxylase (GAD) Antibodies-Mediated Encephalopathy Mimicking Atypical Parkinsonism - Giuseppe Schirò; Matteo Gastaldi; Salvatore Iacono; Silvia Scaranzin; Valentina Picciolo; Valentina Arnao; Anita Ferrari; Cesare Gagliardo; Marco D’Amelio (Neurology International)
Background: Paraneoplastic neurological syndromes (PNSs) are rare conditions characterized by immune-mediated pathogenesis, frequently associated with the presence of a neoplasm. Although a single antineuronal antibody mediates a specific syndrome, atypical manifestations mediated by the same antibody have been described. Methods: The aim of this study was to report on an atypical case of PNS with dual positivity for anti-GAD65 and anti-CRMP5/CV2 antibodies, simultaneously characterized by cognitive decline associated with progressive ataxia and parkinsonism. We also reviewed the current literature for published cases of PNSs with parkinsonism associated with anti-GAD65 and anti- CRMP5/CV2 antibodies. Results: A 68-year-old man with an insidious onset of bradykinesia, cognitive decline, and gait instability that began the year before our evaluation had been diagnosed with parkinsonian syndrome. Analysis of the cerebrospinal fluid showed lymphocytic pleocytosis, and a panel for PNS tested positive for anti-GAD65 and anti- CRMP5/CV2 antibodies. After investigation, a microcitoma was found in the lung. Conclusions: In light of our findings, we suggest considering PNS as an alternative diagnosis to parkinsonism-plus syndromes, in particular if bradykinetic syndrome is accompanied by other clinical manifestations including cognitive decline or ataxia in rapidly deteriorating patients. Earlier detection of PNS would lead to timelier identification of any occult tumors, therein promising improvement in the patient’s prognosis.